Selfish partners: resource partitioning in male coalitions of Asiatic lions. (25th September 2017) - Chakrabarti, Stotra; Jhala, Yadvendradev V
Abstract : For a male lion, teamwork pays off but only to an extent. Using behavioral observations, we show that male Asiatic lions team-up to harness resources effectively, but form hierarchies unlike their egalitarian African cousins. Team members prosper better than loners in gaining and retaining access to females. However, teams of 2 males are optimum as low-ranking members of larger teams fare as poorly as loners. A hitherto unknown behavioral variation in lions highlights the flexibility of group living within species. Abstract: Behavioral plasticity within species is adaptive which directs survival traits to take multiple pathways under varying conditions. Male–male cooperation is an evolutionary strategy often exhibiting an array of alternatives between and within species. African male lions coalesce to safeguard territories and mate acquisition. Unique to these coalitions is lack of strict hierarchies between partners, who have similar resource securities possibly because of many mating opportunities within large female groups. Skewed mating and feeding rights have only been documented in large coalitions where males were related. However, smaller modal prey coupled with less simultaneous mating opportunities for male Asiatic lions in Gir forests, India would likely result in a different coalition structure. Observations on mating events ( n = 127) and feeding incidents ( n = 44) were made on 11 male coalitions and 9 female prides in Gir, to assess resource distribution within and among different sized male coalitions. Information from 39 males was used to estimate annual tenure-holding probabilities. Single males had smaller tenures and appropriated fewer matings than coalition males. Pronounced dominance hierarchies were observed within coalitions, with one partner getting more than 70% of all matings and 47% more food. Competition between coalition partners at kills increased with decline in prey size, increase in coalition size and the appetite states of the males. However, immediate subordinates in coalitions had higher reproductive fitness than single males. Declining benefits to partners with increasing coalition size, with individuals below the immediate subordinates having fitness comparable to single males, suggest to an optimal coalition size of 2 lions. Lions under different competitive selection in Gir show behavioral plasticity to form hierarchical coalitions, wherein partners utilize resources asymmetrically, yet coalesce for personal gains.